4-Azidobenzyl ferrocenylcarbamate as an anticancer prodrug activated under reductive conditions - Kinski, Elisa; Marzenell, Paul; Hofer, Walter; Hagen, Helen; Raskatov, Jevgenij A.; Knaup, Karl; Zolnhofer, Eva; Meyer, Karsten; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2016)
Aminoferrocene-based prodrugs are activated in the presence of cancer-specific amounts of reactive oxygen species, e.g. H2O2, with the formation of products of two types: Fe-containing complexes, which catalyze generation of HO and O2-, and quinone methides, which alkylate glutathione and inhibit the antioxidative system of the cell. Both processes act synergistically by increasing the oxidative stress in cancer cells thereby leading to their death. However, in the activation step including the cleavage of a B-C bond one molecule of H2O2 is consumed that counteracts the desired effect of the products released from aminoferrocenes. We replaced an H2O2-sensitive trigger in original prodrugs with an azide group. This trigger is slowly reduced in the presence of glutathione with the formation of an unstable arylamine intermediate, which decomposes with the release of iron ions and iminoquinone methides. These products induce strong oxidative stress in cells as we confirmed using 2′,7′-dichlorodihydrofluorescin diacetate reagent in combination with flow cytometry. In this case the activation process does not consume H2O2. Correspondingly, we observed that the azide-containing prodrug is substantially more toxic towards human promyelocytic leukemia cell line HL-60 (IC50 = 27 ± 4 μM) than its H2O2-responsive analogue (IC50 > 50 μM).
CRIS-Team Scopus Importer:2020-09-14
Keywords: Azide; Cancer; Ferrocene; Prodrug; Reduction

A New Diagnostic Approach to HLA Testing in Kidney Transplant Patients Using Renal Epithelial Cells - Herrmann, Markus; Bach, Christian; Knaup, Karl; Schiffer, Mario; Spriewald, B.; Wiesener, M. S. (AMERICAN JOURNAL OF TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-10-16

A NEW DIAGNOSTIC APPROACH TO HLA TESTING IN KIDNEY TRANSPLANT RECIPIENTS USING CULTURED URINE DERIVED TUBULAR CELLS - Spriewald, Bernd; Herrmann, Markus; Bach, Christian; Knaup, Karl; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Schiffer, Mario; Wiesener, Michael (Joint 34th European Immunogenetics and Histocompatibility and 31st British Society for Histocompatibility and Immunogenetics Conference, 2020)
CRIS-Team WoS Importer:2020-03-24

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

Autosomal dominant tubulointerstitial kidney diseases (ADTKD) - Knaup, Karl; Wiesener, M. S. (Nephrologe, 2019)
Hereditary kidney diseases, particularly those with onset in adulthood, are underdiagnosed due to various reasons, with the exception of autosomal dominant polycystic kidney disease (ADPKD). Among these the autosomal dominant tubulointerstitial kidney diseases (ADTKD) form the largest heterogeneous group of hereditary diseases in adulthood. In cases of negative or unknown family history and a frequently not carried out kidney biopsy, which additionally often only achieves an insufficient differentiation between ADTKD and other potential disease entities, only a molecular genetic analysis leads to a clear classification of the disease. This article describes the clinical phenotype of ADTKD, the subtypes with the so far identified causal heterozygous mutations in 5 candidate genes, as well as the possible differential diagnoses and pathomechanisms. In addition, the already existing treatment approaches for delaying the progression of renal insufficiency are presented. The future necessary measures and results of clinical and also basic research, which could lead the way to specific and therefore more effective treatment interventions are discussed.
CRIS-Team WoS Importer:2019-03-15

Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04

HIF-1 or HIF-2 induction is sufficient to achieve cell cycle arrest in NIH3T3 mouse fibroblasts independent from hypoxia - Hackenbeck, Thomas; Knaup, Karl; Schietke, Ruth; Schödel, Johannes; Willam, Carsten; Wu, Xiaoqing; Warnecke, Christina; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Cell Cycle, 2009)
Hypoxia is a severe stress which induces physiological and molecular adaptations, where the latter is dominated by the Hypoxia-inducible transcription Factor (HIF). A well described response on cellular level upon exposure to hypoxia is a reversible cell cycle arrest, which probably renders the cells more resistant to the difficult environment. The individual roles of hypoxia itself and of the isoforms HIF-1α and HIF-2α in cell cycle regulation are poorly understood and discussed controversially. In order to characterize the isolated effect of both HIFα isoforms on the cell cycle we generated tetracycline inducible, HIF-1α and -2α expressing NIH3T3 cells. The cDNAs for HIFα were mutated to generate stable and active HIF under normoxia. Upon activation of both HIFα subunits, the total number of living cells was reduced and long-term stimulation of HIF led to complete loss of transgene expression, implicating a strong negative selection pressure. Equally, colony forming activity was reduced by activation of both HIFα subunits. Cell cycle analyses showed that HIF activation resulted in a prominent cell cycle arrest in G1-phase, similarly to the hypoxic effect. Both, HIF-1α and HIF-2α were able to induce the expression of the cyclin-dependent kinase inhibitor p27 on reporter gene and protein level. Our study shows that HIF-1 and HIF-2 can individually arrest the cell cycle independent from hypoxia. These findings have implications for the resistance of tumor cells to the environment and treatment, but also for physiological cells. Importantly, recent approaches to stabilize HIFα in normoxia could have deleterious effects on proliferating tissues. ©2009 Landes Bioscience.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Cell cycle regulation; G; Hypoxia; Hypoxia-inducible factor (HIF); p27; Tetracycline-inducible; Tumor resistance; Tumorigenesis; VHL

HIF is not essential for suppression of experimental tumor growth by mTOR inhibition - Knaup, Karl; Günther, Regina; Stoeckert, Johanna; Monti, Juliana M.; Eckardt, Kai-Uwe; Wiesener, Michael (Journal of Cancer, 2017)
The Hypoxia Inducible Transcription Factor (HIF) is the master regulator of cellular response to hypoxic adaptation. Solid tumors inevitably harbour hypoxic regions with subsequent stabilization and activation of HIF and HIF target genes due to poor vascularization and rapid growth. The mammalian target of rapamycin (mTOR) is a global regulator of cellular growth and proliferation, which can also regulate HIF expression independantly of hypoxia via specific activation of cellular translation and transcription. An effective blockade of mTOR results in attenuation of HIF under hypoxic conditions in vitro. This mechanism could enable a simultaneous inhibition of both the mTOR- and the HIF-pathway, resulting in an effective tool for cancer targeting. We set out to analyze the effect of mTOR inhibition and the involvement of mTOR regulation on HIF in vivo in a subcutaneous xenograft model in nude mice. Our results demonstrate that mTOR inhibition in our model leads to a clear reduction in tumor growth of various cellular origins, most likely due to inhibition of cellular proliferation. Moreover, these effects can also be achieved independently of the HIF status of the tumor cells. The HIF levels per se seem to remain unaffected by mTOR inhibition, probably due to the profound hypoxic environment in these threedimensional structures, consequently leading to a strong HIF stabillization. Therefore, treatment of these experimental tumors with mTOR inhibitors is an effective tool to achieve size regression. The involvement of and the effect on HIF in this in vivo setting is nevertheless negligible.
EVALuna2:3992

Hypoxia controls expression of kidney-pathogenic MUC1 variants - Naas, Stephanie; Krüger, René; Knaup, Karl; Naas, Julia; Grampp, Steffen; Schiffer, Mario; Wiesener, Michael; Schödel, Johannes (Life Science Alliance, 2023)
The interplay between genetic and environmental factors influences the course of chronic kidney disease (CKD). In this context, genetic alterations in the kidney disease gene MUC1 (Mucin1) predispose to the development of CKD. These variations comprise the polymorphism rs4072037, which alters splicing of MUC1 mRNA, the length of a region with variable number of tandem repeats (VNTR), and rare autosomal-dominant inherited dominant-negative mutations in or 59 to the VNTR that causes autosomal dominant tubulointerstitial kidney disease (ADTKD-MUC1). As hypoxia plays a pivotal role in states of acute and chronic kidney injury, we explored the effects of hypoxia-inducible transcription factors (HIF) on the expression of MUC1 and its pathogenic variants in isolated primary human renal tubular cells. We defined a HIF-binding DNA regulatory element in the promoter-proximal region of MUC1 from which hypoxia or treatment with HIF stabilizers, which were recently approved for an anti-anemic therapy in CKD patients, increased levels of wild-type MUC1 and the disease-associated variants. Thus, application of these compounds might exert unfavorable effects in patients carrying MUC1 risk variants.
CRIS-Team Scopus Importer:2023-08-11

Hypoxia hits APOL1 in the kidney - Grampp, Steffen; Krüger, René; Lauer, Victoria; Uebel, Sebastian; Knaup, Karl; Naas, Julia; Höffken, Verena; Weide, Thomas; Schiffer, Mario; Naas, Stephanie; Schödel, Johannes (Kidney International, 2023)
Individuals of African ancestry carrying two pathogenic variants of apolipoprotein 1 (APOL1) have a substantially increased risk for developing chronic kidney disease. The course of APOL1 nephropathy is extremely heterogeneous and shaped by systemic factors such as a response to interferon. However, additional environmental factors operating in this second-hit model have been less well defined. Here, we reveal that stabilization of hypoxia-inducible transcription factors (HIF) by hypoxia or HIF prolyl hydroxylase inhibitors activates transcription of APOL1 in podocytes and tubular cells. An active regulatory DNA-element upstream of APOL1 that interacted with HIF was identified. This enhancer was accessible preferentially in kidney cells. Importantly, upregulation of APOL1 by HIF was additive to the effects of interferon. Furthermore, HIF stimulated expression of APOL1 in tubular cells derived from the urine of an individual carrying a risk variant for kidney disease. Thus, hypoxic insults may serve as important modulators of APOL1 nephropathy.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chronic kidney disease; hypoxia; podocyte; transcription regulation

Hypoxia-inducible factor-1α is a critical transcription factor for IL-10-producing B cells in autoimmune disease - Meng, Xianyi; Groetsch, Bettina; Luo, Yubin; Knaup, Karl; Wiesener, Michael; Chen, Xiao-Xiang; Jantsch, Jonathan; Fillatreau, Simon; Schett, Georg; Bozec, Aline (Nature Communications, 2018)
Hypoxia-inducible factors (HIFs) are key elements for controlling immune cell metabolism and functions. While HIFs are known to be involved in T cells and macrophages activation, their functions in B lymphocytes are poorly defined. Here, we show that hypoxia-inducible factor-1? (HIF-1?) contributes to IL-10 production by B cells. HIF-1? regulates IL-10 expression, and HIF-1?-dependent glycolysis facilitates CD1dhiCD5+ B cells expansion. Mice with B cell-specific deletion of Hif1a have reduced number of IL-10-producing B cells, which result in exacerbated collagen-induced arthritis and experimental autoimmune encephalomyelitis. Wild-type CD1dhiCD5+ B cells, but not Hif1a-deficient CD1dhiCD5+ B cells, protect recipient mice from autoimmune disease, while the protective function of Hif1a-deficient CD1dhiCD5+ B cells is restored when their defective IL-10 expression is genetically corrected. Taken together, this study demonstrates the key function of the hypoxia-associated transcription factor HIF-1? in driving IL-10 expression in CD1dhiCD5+ B cells, and in controlling their protective activity in autoimmune disease.
EVALuna2:13529

Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Knaup, Karl; Büttner-Herold, Maike; Dieterle, Anne; Stoeckert, Johanna; Riedl, Bernhard; Morath, Christian; Wald, Alexandra; Vondran, Florian; Braun, Felix; Schödel, Johannes; Schüler, Markus; et al. (American Journal of Transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor's disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient ' s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
CRIS-Team WoS Importer:2020-01-31

MOLECULAR DIAGNOSIS OF KIDNEY TRANSPLANT FAILURE BY THE URINE - Knaup, Karl; Wiesener, A.; Buettner-Herold, M.; Dieterle, A.; Morath, C.; Vondran, F. W. R.; Wald, A.; Braun, F.; Schüler, Markus; Schödel, Johannes; Schiffer, Mario; Reis, André; et al. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Mutations in PIK3C2A cause syndromic short stature, skeletal abnormalities, and cataracts associated with ciliary dysfunction - Tiosano, Dov; Baris, Hagit N.; Chen, Anlu; Hitzert, Marrit M.; Schüler, Markus; Gulluni, Federico; Wiesener, Antje; Bergua, Antonio; Mory, Adi; Copeland, Brett; Gleeson, Joseph G.; Rump, Patrick; et al. (PLoS Genetics, 2019)
PIK3C2A is a class II member of the phosphoinositide 3-kinase (PI3K) family that catalyzes the phosphorylation of phosphatidylinositol (PI) into PI(3)P and the phosphorylation of PI(4)P into PI(3,4)P2. At the cellular level, PIK3C2A is critical for the formation of cilia and for receptor mediated endocytosis, among other biological functions. We identified homozygous loss-of-function mutations in PIK3C2A in children from three independent consanguineous families with short stature, coarse facial features, cataracts with secondary glaucoma, multiple skeletal abnormalities, neurological manifestations, among other findings. Cellular studies of patient-derived fibroblasts found that they lacked PIK3C2A protein, had impaired cilia formation and function, and demonstrated reduced proliferative capacity. Collectively, the genetic and molecular data implicate mutations in PIK3C2A in a new Mendelian disorder of PI metabolism, thereby shedding light on the critical role of a class II PI3K in growth, vision, skeletal formation and neurological development. In particular, the considerable phenotypic overlap, yet distinct features, between this syndrome and Lowe's syndrome, which is caused by mutations in the PI-5-phosphatase OCRL, highlight the key role of PI metabolizing enzymes in specific developmental processes and demonstrate the unique non-redundant functions of each enzyme. This discovery expands what is known about disorders of PI metabolism and helps unravel the role of PIK3C2A and class II PI3Ks in health and disease.
CRIS-Team Scopus Importer:2019-05-28

Pgam5 released from damaged mitochondria induces mitochondrial biogenesis via Wnt signaling - Bernkopf, Dominic; Jalal, Kowcee; Brückner, Martina; Knaup, Karl; Gentzel, Marc; Schambony, Alexandra; Behrens, Jürgen (The Journal of Cell Biology, 2018)
Mitochondrial abundance is dynamically regulated and was previously shown to be increased by Wnt/β-catenin signaling. Pgam5 is a mitochondrial phosphatase which is cleaved by the rhomboid protease presenilin-associated rhomboid-like protein (PARL) and released from membranes after mitochondrial stress. In this study, we show that Pgam5 interacts with the Wnt pathway component axin in the cytosol, blocks axin-mediated β-catenin degradation, and increases β-catenin levels and β-catenin-dependent transcription. Pgam5 stabilized β-catenin by inducing its dephosphorylation in an axin-dependent manner. Mitochondrial stress triggered by carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment led to cytosolic release of endogenous Pgam5 and subsequent dephosphorylation of β-catenin, which was strongly diminished in Pgam5 and PARL knockout cells. Similarly, hypoxic stress generated cytosolic Pgam5 and led to stabilization of β-catenin, which was abolished by Pgam5 knockout. Cells stably expressing cytosolic Pgam5 exhibit elevated β-catenin levels and increased mitochondrial numbers. Our study reveals a novel mechanism by which damaged mitochondria might induce replenishment of the mitochondrial pool by cell-intrinsic activation of Wnt signaling via the Pgam5-β-catenin axis.
EVALuna2:34942

Prevalence of hereditary tubulointerstitial kidney diseases in the German Chronic Kidney Disease study - Popp, Bernt; Ekici, Arif Bülent; Knaup, Karl; Schneider, Karen; Uebe, Steffen; Park, Jonghun; Bafna, Vineet; Meiselbach, Heike; Eckardt, Kai-Uwe; Schiffer, Mario; Wiesmann da Silva Reis, André; Kraus, Cornelia; et al. (European Journal of Human Genetics, 2022)
Hereditary chronic kidney disease (CKD) appears to be more frequent than the clinical perception. Exome sequencing (ES) studies in CKD cohorts could identify pathogenic variants in similar to 10% of individuals. Tubulointerstitial kidney diseases, showing no typical clinical/histologic finding but tubulointerstitial fibrosis, are particularly difficult to diagnose. We used a targeted panel (29 genes) and MUC1-SNaPshot to sequence 271 DNAs, selected in defined disease entities and age cutoffs from 5217 individuals in the German Chronic Kidney Disease cohort. We identified 33 pathogenic variants. Of these 27 (81.8%) were in COL4A3/4/5, the largest group being 15 COL4A5 variants with nine unrelated individuals carrying c.1871G>A, p.(Gly624Asp). We found three cysteine variants in UMOD, a novel missense and a novel splice variant in HNF1B and the homoplastic MTTF variant m.616T>C. Copy-number analysis identified a heterozygous COL4A5 deletion, and a HNF1B duplication/deletion, respectively. Overall, pathogenic variants were present in 12.5% (34/271) and variants of unknown significance in 9.6% (26/271) of selected individuals. Bioinformatic predictions paired with gold standard diagnostics for MUC1 (SNaPshot) could not identify the typical cytosine duplication ("c.428dupC") in any individual, implying that ADTKD-MUC1 is rare. Our study shows that >10% of selected individuals carry disease-causing variants in genes partly associated with tubulointerstitial kidney diseases. COL4A3/4/5 genes constitute the largest fraction, implying they are regularly overlooked using clinical Alport syndrome criteria and displaying the existence of phenocopies. We identified variants easily missed by some ES pipelines. The clinical filtering criteria applied enriched for an underlying genetic disorder.
CRIS-Team WoS Importer:2022-09-23

Progressive Kidney Failure by Angiotensinogen Inactivation in the Germline - Wopperer, Florian; Olinger, Eric; Wiesener, Antje; Broeker, Katharina A.E.; Knaup, Karl; Schaefer, Jan Thomas; Galiano, Matthias; Schneider, Karen; Schiffer, Mario; Büttner-Herold, Maike; Reis, André; Schmieder, Roland; et al. (Hypertension, 2024)
BACKGROUND: Autosomal recessive renal tubular dysgenesis is a rare, usually fatal inherited disorder of the REN (renin)angiotensin system. Herein, we report an adolescent individual experiencing an unknown chronic kidney disease and aim to provide novel insights into disease mechanisms. METHODS: Exome sequencing for a gene panel associated with renal disease was performed. The REN-angiotensin system was assessed by comprehensive biochemical analysis in blood. REN expression was determined in primary tubular cells by quantitative polymerase chain reaction and in situ hybridization on kidney biopsy samples. Allele frequencies of heterozygous and biallelic deleterious variants were determined by analysis of the Genomics England 100,000 Genomes Project. RESULTS: The patient was delivered prematurely after oligohydramnios was detected during pregnancy. Postnatally, he recovered from third-degree acute kidney injury but developed chronic kidney disease stage G3b over time. Exome sequencing revealed a previously reported pathogenic homozygous missense variant, p.(Arg375Gln), in the AGT (angiotensinogen) gene. Blood AGT concentrations were low, but plasma REN concentration and gene expression in kidney biopsy, vascular, and tubular cells revealed strong upregulation of REN. Angiotensin II and aldosterone in blood were not abnormally elevated. CONCLUSIONS: Renal tubular dysgenesis may present as chronic kidney disease with a variable phenotype, necessitating broad genetic analysis for diagnosis. Functional analysis of the renin-angiotensin system in a patient with AGT mutation revealed novel insights regarding compensatory upregulation of REN in vascular and tubular cells of the kidney and in plasma in response to depletion of AGT substrate as a source of Ang II (similarly observed with hepatic AGT silencing for the treatment of hypertension).
CRIS-Team Scopus Importer:2024-07-26
Keywords: angiotensinogen; exome; mass spectrometry; mutation; renin-angiotensin system

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule - Jobst-Schwan, Tilman; Knaup, Karl; Nielsen, Rikke; Hackenbeck, Thomas; Büttner-Herold, Maike; Lechler, Philipp; Kroening, Sven; Goppelt-Strübe, Margarete; Schlötzer-Schrehardt, Ursula; Fuernrohr, Barbara G.; Voll, Reinhard E.; Amann, Kerstin Ute; et al. (American Journal of Physiology-Renal Physiology, 2013)
The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localization as survivin. Immunolabeling for survivin in different species confirmed survivin signal localizing to the apical membrane of the proximal tubule. Immunoelectron microscopy also showed apical localization of survivin in human kidneys. Furthermore, in polarized human primary tubular cells endogenous as well as external recombinant survivin is stored in the apical region of the cells. Costaining of survivin and megalin by immunohistochemistry and immunoelectron microscopy confirmed colocalization. Finally, by surface plasmon resonance we were able to demonstrate that survivin binds megalin and cubilin and that megalin knockout mice lose survivin through the urine. Survivin accumulates at the apical membrane of the renal tubule by reuptake, which is achieved by the endocytic receptor megalin, collaborating with cubilin. For this to occur, survivin will have to circulate in the blood and be filtered into the primary urine. It is not known at this stage what the functional role of tubular survivin is. However, a small number of experimental and clinical reports implicate that renal survivin is important for functional integrity of the kidney. © 2013 by the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Acute kidney injury; Apoptosis; Glomerular filtration; Lysosomes; Proteinuria